Urinary tract infection in the setting of vesicoureteral reflux - Garcia-Roig, Michael L. (F1000Res, 2016)
Vesicoureteral reflux (VUR) is the most common underlying etiology responsible for febrile urinary tract infections (UTIs) or pyelonephritis in children. Along with the morbidity of pyelonephritis, long-term sequelae of recurrent renal infections include renal scarring, proteinuria, and hypertension. Treatment is directed toward the prevention of recurrent infection through use of continuous antibiotic prophylaxis during a period of observation for spontaneous resolution or by surgical correction. In children, bowel and bladder dysfunction (BBD) plays a significant role in the occurrence of UTI and the rate of VUR resolution. Effective treatment of BBD leads to higher rates of spontaneous resolution and decreased risk of UTI.